Association of soft drinks and 100% fruit juice consumption with risk of cancer: a systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Honghao Lai; Ning Ma; Dan Li; Xiyuan Deng; Xiaoman Wang; Qian Zhang; Qiuyu Yang; Qi Wang; Hongfei Zhu; Mengting Li; Xiao Cao; et al. (BMC, 2023)
Abstract Background Studies of the associations between soft drinks and the risk of cancer showed inconsistent results. No previous published systematic reviews and meta-analysis has investigated a dose-response association between exposure dose and cancer risk or assessed the certainty of currently available evidence. Therefore, we aim to demonstrate the associations and assessed the certainty of the evidence to show our confidence in the associations. Methods We searched Embase, PubMed, Web of Science, and the Cochrane Library from inception to Jun 2022, to include relevant prospective cohort studies. We used a restricted cubic spline model to conduct a dose-response meta-analysis and calculated the absolute effect estimates to present the results. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to assess the certainty of the evidence. Results Forty-two articles including on 37 cohorts enrolled 4,518,547 participants were included. With low certainty evidence, increased consumption of sugar-sweetened beverages (SSBs) per 250 mL/day was significantly associated with a 17% greater risk of breast cancer, a 10% greater risk of colorectal cancer, a 30% greater risk of biliary tract cancer, and a 10% greater risk of prostate cancer; increased consumption of artificially sweetened beverages (ASBs)re per 250 mL/day was significantly associated with a 16% greater risk of leukemia; increased consumption of 100% fruit juice per 250 mL/day was significantly associated with a 31% greater risk of overall cancer, 22% greater risk of melanoma, 2% greater risk of squamous cell carcinoma, and 29% greater risk of thyroid cancer. The associations with other specific cancer were no significant. We found linear dose-response associations between consumption of SSBs and the risk of breast and kidney cancer, and between consumption of ASBs and 100% fruit juices and the risk of pancreatic cancer. Conclusions An increment in consumption of SSBs of 250 mL/day was positively associated with increased risk of breast, colorectal, and biliary tract cancer. Fruit juices consumption was also positively associated with the risk of overall cancer, thyroid cancer, and melanoma. The magnitude of absolute effects, however, was small and mainly based on low or very low certainty of evidence. The association of ASBs consumption with specific cancer risk was uncertain. Trial registration PROSPERO: CRD42020152223